Analisis Penerapan Prinsip Good Corporate Governance (GCG) Dalam Meningkatkan Kinerja Karyawan Pada PT. Bank Sumut KCP Syariah Marelan Raya - M. Iqbal; Wahyudi Nasution; Okky Budi Nurlita; Rizka Dwi Rahmadayana (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to find out in depth the application of Good Corporate Governance (GCG) principles in improving the performance of PT employees. North Sumatra Bank. By analyzing the principles of implementing GCG, this research will identify the impact of implementing GCG on employee performance. This research uses a qualitative research method which is a research design that has a natural nature, in the sense that the researcher is not manipulating research but conducting a study of a phenomenon. It is hoped that the results of this research will provide in-depth insight into the application of Good Corporate Governance principles in improving the performance of PT employees. Bank Sumut KCP Syariah Marelan Raya.